'SCHRIFT ZAGT BLASSES UNBEKANNT': THE POETRY OF AUGUST STRAMM (1874–1915). (April 2013) - Kramer, Andreas
Abstract : This essay examines the radical innovations in language and form on display in Stramm's poems, from the early nature poems and 'Du. Liebesgedichte' to the late war poems. It focuses in particular on the radical forms of experience and subjectivity that such innovations convey. The essay is organized around various tropes of movement and mobility, offering in-depth readings of key poems to discuss how Stramm's spare yet formalized language points to mobile, shifting and traumatic subjectivities, all the way to the final war poems in which the twin poles of Expressionism – modernist alienation and redemptive articulation – seem to coincide.